Induced Pluripotent Stem Cell-Derived Mesenchymal Stem Cells Hold Lower Heterogeneity and Great Promise in Biological Research and Clinical Applications - Zhang, Juan; Chen, Mingzhuang; Liao, Jinqi; Chang, Chongfei; Liu, Yuqing; Padhiar, Arshad Ahmed; Zhou, Yan; Zhou, Guangqian (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSC) isolated from different tissue sources exhibit multiple biological effects and have shown promising therapeutic effects in a broad range of diseases. In order to fulfill their clinical applications in context of precision medicine, however, more detailed molecular characterization of diverse subgroups and standardized scalable production of certain functional subgroups would be highly desired. Thus far, the generation of induced pluripotent stem cell (iPSC)-derived MSC (iMSC) seems to provide the unique opportunity to solve most obstacles that currently exist to prevent the broad application of MSC as an advanced medicinal product. The features of iMSC include their single cell clone origins, and defined and controllable cultural conditions for their derivation and proliferation. Still, comprehensive research of the molecular and functional heterogeneity of iMSC, just like MSC from any other tissue types, would be required. Furthered on previous efforts on iMSC differentiation and expansion platform and transcriptomic studies, advantages of single cell multi-omics analysis and other up-to-dated technologies would be taken in order to elucidate the molecular origin and regulation of heterogeneity and to obtain iMSC subgroups homogeneous enough for particular clinical conditions. In this perspective, the current obstacles in MSC applications, the advantages of iMSC over MSC and their implications for biological research and clinical applications will be discussed.